Experiences and Level of Acceptance of Students in using Knowledge Hub as Learning Management System - Galdonez, Dominic Patric G; Aganon, Francine Valerie B.; Gavila, Princess C; Jose, Cathrina Mae C (Social Sciences, Humanities and Education Journal (SHE Journal), 2023)
This study aimed to examine and analyze the experiences and acceptance levels of students at the Philippine Science High School - Ilocos Region Campus (PSHS-IRC) in using the Pisay Knowledge Hub (KHub) as a Learning Management System (LMS) during the academic year 2020-2021. A mixed-method research approach was utilized. The Likert scale interpretation was employed to understand the level of acceptance, and the Technology Acceptance Model was implemented to comprehend the students' experiences. Based on the gathered data, the study revealed that students generally accepted and agreed with the use of KHub as a LMS, as evidenced by the following aspects: satisfaction (x=3.67), usefulness (x=3.77), and ease of use (x=3.73). The study also identified four themes that shaped the students' experiences in using KHub: strengths, weaknesses, challenges, and recommendations. Strengths refer to the positive experiences that students liked about using the LMS. In contrast, weaknesses explain the unfavorable experiences. Regarding the theme of challenges, it encompasses the technical issues and features of the LMS that posed problems when used. Lastly, the recommendations’ theme relates to the students' suggestions for improvement. Considering these findings, the following recommendations are made conduct further investigation and analysis of teachers' experiences in using LMSKHub, address the challenges experienced by students in using instructional technology, maintain and continue the use of KHub as a Learning Management System in teaching and learning, and provide intensive training on it.